(untitled) (Indian Journal of Animal Production and Management, 2025)
The present study was undertaken to analyze the socio-economic characteristics of Bargur buffalo farmers in their native tract. Data were collected from 100 selected respondents using a pre-tested and structured interview schedule over five months. The results revealed that most of the respondents were female (57%), highlighting the significant role of women in buffalo-rearing activities. Most farmers were middle-aged or elderly (87%) and belonged to nuclear family structures (57%). A large proportion (88%) were from the Backward Class and possessed marginal landholdings (83%). Regarding educational status, 61% had primary education, and 40% were illiterate. Agriculture was the primary occupation for 97% of the respondents, and the annual income of most farmers ranged from low to moderate income. Livestock ownership was generally small, with 58% of farmers maintaining three to five buffaloes each. Notably, 76% of the respondents had more than 10 years of experience in buffalo rearing, reflecting the traditional nature of the occupation. However, none of the respondents had received formal training in buffalo management or husbandry. These findings emphasize the need for targeted capacity-building programs and strengthened extension services to enhance productivity and ensure livelihood security among farmers.